Urine concentration should be taken into account when interpreting pyuria in infants. - Alam, S; Voort, J; Butler, C (BMJ Publishing Group, 2017)
The relationship between pyuria and true urinary tract infection (UTI) remains controversial. Most studies have assessed pyuria using manual microscopy in centrifuged urine. However, standard practice at most centres now involves automated urinalysis of uncentrifuged urine, thus pyuria in dilute samples may have more significance than pyuria in concentrated urine samples. It may therefore be important to consider the possible impact of urine concentration on the significance of white cell counts (WCC) or leucocyte esterase (LE) assessment.